Cognitive Representation and Its Relation with Academic Self-Efficacy for University Students (Raparin Journal of Humanities (RJH), 2025)
The goals of present research are Getting to know the cognitive representation، and academic self-efficacy level among university students for the sample as a whole. It also aimed to know the relationship between cognitive representation and academic self-efficacy among Preparatory school students. And the last aim of this research is Getting to know the nature of the differences in cognitive representation، and academic self-efficacy among University students according to the variable of gender (male & female)، academic specialization (scientific & literary)، and Academic stage (first stage، fourth stage). In order to achieving the aims of the research، the researchers are prepared a cognitive representation scale consisting of (48) paragraphs، and used the academic self-efficacy scale developed by (Abdul-hay، 2013)، which was used to measure the level of academic self-efficacy، and consists of (37) paragraphs. The sample of the study consisted of (450) students; (133) males and (317) females، Of day- governmental organizations University students - both males and females for academic year (2023-2024). The researchers used in the treatment of a number of statistical methods، namely: duplicates، T-test for two independent samples (Two-Sample T.test)، T-test for one sample، Pearson 's correlation coefficient). The results showed the research sample of university students have a high level of cognitive representation and academic self-efficacy. It also showed there was no relationship between cognitive representation and academic self-efficacy among the simple of the research.